2005
DOI: 10.1038/ng1563
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome analyses using BAC microarrays identify evolutionary conservation of tissue-specific methylation of SHANK3

Abstract: CpG islands are present in one-half of all human and mouse genes and typically overlap with promoters or exons. We developed a method for high-resolution analysis of the methylation status of CpG islands genome-wide, using arrays of BAC clones and the methylation-sensitive restriction enzyme NotI. Here we demonstrate the accuracy and specificity of the method. By computationally mapping all NotI sites, methylation events can be defined with single-nucleotide precision throughout the genome. We also demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 41 publications
4
100
0
2
Order By: Relevance
“…CpG island arrays represent a high-throughput technology for the discovery of CpG island loci frequently hypermethylated during disease progression (Yan et al, 2000;Ching et al, 2005). Gene profiling analyses of cancer cells after exposure to demethylating agents may also uncover critical genes susceptible to be epigenetically silenced (Liang et al, 2002).…”
mentioning
confidence: 99%
“…CpG island arrays represent a high-throughput technology for the discovery of CpG island loci frequently hypermethylated during disease progression (Yan et al, 2000;Ching et al, 2005). Gene profiling analyses of cancer cells after exposure to demethylating agents may also uncover critical genes susceptible to be epigenetically silenced (Liang et al, 2002).…”
mentioning
confidence: 99%
“…One of these genome wide approaches known as Restriction Landmark Genome Scanning (RLGS) has enabled to identify in six mice tissues a large number of differentially methylated regions (TDMs) which exhibit a tissue-specific expression pattern that is consistent with methylation status and a role in tissue differentiation [50]. Furthermore, Ching et al [51], by using BAC microarray have identified CpG island loci that are methylated in a tissue-specific manner in normal human tissues, including SHANK3 whose differential methylation in different tissues was also evolutionary conserved.…”
Section: Cpg Dinucleotides Location and Func-tionmentioning
confidence: 99%
“…However, the DNA methylation profiles obtained have not been directly related to gene function (Ching et al 2005;Eckhardt et al 2006;Khulan et al 2006). The limited number of loci or regions available for genome-wide analysis of normal cells or tissues and the existence of method biases can affect the implementation of methylated profiles (for review, see Khulan et al 2006).…”
mentioning
confidence: 99%